Educating Rubber Farmers on The Use of Chemical Substances Affecting the Generation of B3 in Panca Desa Banyuasin I - Inike Fratiwi; Asia Afriyani; Ratih Wijayanti; Muhammad Agus (International Journal Of Community Service, 2025)
A program to educate rubber farmers on the use of chemicals with B3 impacts has been implemented in Panca Desa Banyuasin I by Serasan University. The program aimed to increase farmers' awareness and knowledge of the dangers of hazardous chemicals and encourage the adoption of more environmentally friendly agricultural practices. Several rubber farmers participated in extension and training that included materials on chemical management, organic fertilizer use, and environmentally friendly farming. The results of the activities showed that farmers' level of understanding of the materials improved significantly. However, farmers still need further guidance to completely abandon the use of chemicals. Initial changes in farming practices are starting to be seen, where farmers are starting to reduce direct contact with chemicals and consider organic alternatives. This activity is having a positive impact in minimizing health and environmental risks in Panca Desa Banyuasin I. However, to ensure sustainability, further assistance, financial support, and strengthening of policies related to environmentally friendly agricultural practices are needed.